2020
DOI: 10.3389/fmolb.2020.544895
|View full text |Cite
|
Sign up to set email alerts
|

PCOLCE Is Potent Prognostic Biomarker and Associates With Immune Infiltration in Gastric Cancer

Abstract: BackgroundThe exact biological role of PCOLCE was not yet clear and there were few reports study the correlation of PCOLCE gene expression level with the occurrence and development of gastric cancer.MethodsThe expression of PCOLCE was analyzed by performing the Oncomine and Ualcan database. We evaluated the function of PCOLCE on clinical prognosis with the use of Kaplan–Meier plotter database. The relationship between PCOLCE and cancer immune in filtrates was researched by Tumor Immune Estimation Resource (TIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Xiang and his team reported that PCOLCE was elevated in gastric cancer and was associated with poor prognosis of gastric cancer patients. 11 The same study also revealed that PCOLCE expression was positively correlated with the level of dendritic cells and macrophages in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Xiang and his team reported that PCOLCE was elevated in gastric cancer and was associated with poor prognosis of gastric cancer patients. 11 The same study also revealed that PCOLCE expression was positively correlated with the level of dendritic cells and macrophages in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 82%
“…A recent study revealed that high expression of PCOLCE affected lymph node metastasis and was associated with poor prognosis in ovarian and gastric cancer. 11 Wang reported that PCOLCE expression was elevated by TWIST1 in osteosarcoma, and identified the N-glycosylation of PCOLCE as a critical promoter of metastasis of osteosarcoma. 10 This research is the first to systematically assess the roles and mechanisms of PCOLCE in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated neutrophils (TANs) were proposed to induce lymphangiogenesis and angiogenesis, and it was shown that local infiltration of certain types of TANs may play a role in the metastasis in GC (Hiramatsu et al, 2018). Infiltration of dendritic cells in gastric cancer and lymph nodes of GC patients are well known (Tsujitani et al, 1992;Tsujitani et al, 1995), and its infiltrating level in GC was also found to be closely correlated with macrophage infiltration (Xiang et al, 2020). One study found that higher level of dendritic cell infiltration was associated with longer OS (Higgins and Thompson, 2002;Hu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that in ltration of M 0 macrophages predicts worse OS in LUAD patients 39 . Xiang et al have con rmed that PCOLCE could become a potent prognostic biomarker due to its association with the in ltrating TAM in gastric cancer 40 . Accumulating evidence suggests that the recruitment of Treg helps cancer cells to immune escape through various mechanisms 41 , and Treg accumulation could predict worse prognosis in several tumors of epithelial origin [42][43][44] .…”
Section: Discussionmentioning
confidence: 99%